Persistence of Robust Humoral Immune Response in Coronavirus Disease 2019 Convalescent Individuals Over 12 Months After Infection. (10th December 2021) - Miyakawa, Kei; Kubo, Sousuke; Stanleyraj Jeremiah, Sundararaj; Go, Hirofumi; Yamaoka, Yutaro; Ohtake, Norihisa; Kato, Hideaki; Ikeda, Satoshi; Mihara, Takahiro; Matsuba, Ikuro; Sanno, Naoko; Miyakawa, Masaaki; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection elicits varying degrees of protective immunity conferred by neutralizing antibodies (nAbs). In this study, we report the persistence of nAb responses over 12 months after infection despite their decreasing trend noticed from 6 months. Methods: The study included sera from 497 individuals who had been infected with SARS-CoV-2 between January and August 2020. Samples were collected at 6 and 12 months after onset. The titers of immunoglobulin (Ig)G to the viral nucleocapsid protein (NP) and receptor-binding domain (RBD) of the spike protein were measured by chemiluminescence enzyme immunoassay. The nAb titer was determined using lentivirus-based pseudovirus or authentic virus. Results: Antibody titers of NP-IgG, RBD-IgG, and nAbs were higher in severe and moderate cases than in mild cases at 12 months after onset. Although the nAb levels were likely to confer adequate protection against wild-type viral infection, the neutralization activity to recently circulating variants in some of the mild cases (~30%) was undermined, implying the susceptibility to reinfection with the variants of concerns (VOCs). Conclusions: Coronavirus disease 2019 convalescent individuals have robust humoral immunity even at 12 months after infection albeit that the medical history and background of patients could affect the function and dynamics of antibody response to the VOCs. Abstract : We investigated the magnitude of the humoral immunity to SARS-CoV-2 one year after infection. We found that neutralizing antibodies maintained an effective titer after one year, and that patients who recovered from severe illness had higher levels of the antibodies